CGIAR Science Group Evaluations: Climate Change - Humphrey, Sarah; Negroustoueva, Svetlana (CGIAR Independent Advisory and Evaluation Service, 2025)
The CGIAR 2030 Research and Innovation Strategy identifies adaptation and mitigation as part of five Sustainable Development Goal (SDG)-focused Impact Areas. The Strategy suggests how CGIAR’s research, innovation and capacity development can contribute toward achieving collective global targets for climate change adaptation and mitigation. CGIAR’s action on climate change addresses the risks to food systems, the impact of food systems emissions, and the potential for integrated solutions.